Performance Comparison of Schedulers in MmWave Communication using NS-3 - Victor Lamboy Sinaga; Rakhmat Yuniarto; Tofan Hermawan; Ruki Harwahyu; Riri Fitri Sari (Proceeding of the Electrical Engineering Computer Science and Informatics, 2020)
Millimeter-wave (mmWave) has proven to provide the bandwidth requirement for the new radio (NR) on 5G. MmWave has been developed as a new technology to support enhanced mobile broadband (eMBB), massive machine-type communication (mMTC), and ultra-reliable low latency communication (URLLC). Since using a high frequency, mmWave also has some disadvantages that could not be avoided, such as small coverage, high signal attenuation, limited against some obstacles, and sensitive to the influence of signal quality. This paper discusses the effect of signal quality on 5G performance using mmWave while sending or receiving packet data by using three types of the scheduler, such as Round Robin, Proportional Fairness, and Max Rate scheduler. Signal quality will impact the value of modulation and coding scheme (MCS) that will be used. Our experiments using NS-3 based on the scenario showed that in the same location and number of UEs, performance throughput using Round Robin and Max Rate with excellent signal strength could reach the maximum throughput. The use of Proportional Fairness could lead only to reaching 50% of the maximum throughput. On the other hand, the use of the Proportional Fairness scheduler causes the weak signal to be unstable. Using Round Robin scheduler, the throughput is more stable. Different from the result using the Max Rate scheduler, the UE with the best signal quality compared to other UEs, was the only UE that get the resources allocation.